ChemInform Abstract: Wacker‐Type Oxidation of Internal Alkenes Using Pd(Quinox) and TBHP. Issue 28 (21st June 2013) - DeLuca, Ryan J.; Edwards, Jennifer L.; Steffens, Laura D.; Michel, Brian W.; Qiao, Xiaoxiao; Zhu, Chunyin; Cook, Silas P.; Sigman, Matthew S.
Abstract The reaction is a useful complement to the traditional Tsuji—Wacker oxidation of internal alkenes.